THE PARADOXICAL POLICY OF USSR MEDIA CONTROLS AFTER 1985 AND GORBACHEV VS THE SOVIET POWER STRUCTURE: LIBERALIZATION OF MEDIA - Saidov Ilhomjon Muhiddinovich; Yuldashev Akmal Kurbanbayevich (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses changes in the media policy of the Soviet Union since 1985. In this, the political path of the new general secretary of the Communist Party, M.S. Gorbachev, and the change of censorship, which has been preserved for years, will be highlighted. In politics, opposite political situations of press and power structures are observed. Therefore, the influence of this new policy on the economic crisis of the Former Union was increasing. The development of the media and the warm reception of foreign media in the territory of the USSR accelerated these processes.